To Mourn a Time Still Here - Betist, Caressa (My University, 2025)
The project I exhibited during the Kuvan Kevät Master graduation show "Youth Singing in a Bunker" was a three-channel video installation with 5.1 surround sound that was played on loop. Upon entering the rather small space, you would immediately walk past one of the three 284 x 178 cm wooden screens that were hung in the space. Positioned at a 90 degree angle from each other. This way the three screens would surround the audience once stepping into the exhibition space. On the center screen was a band. They were playing an original song inside a bunker. A slow song. On both sides of the band – on the two side screens – you could see groups of people watching the band perform this song. Some were standing, some sat on the ground, and others leaned against the grey rock walls. They listened to the song while the drum rhythm filled the space. Towards the middle of the song, a few people on the side channels started to sing along to the lyrics of the chorus-line: ”Luckily, time passes and things change, but sadly, time passes and things change.” The first chapter of this thesis “Angst, my dear” focuses on the personal and generational sense of existential angst caused by the climate crisis. An experience of angst over losing the present, fueled by uncertainty over the future. Sharing theories by scholars it details how Youth Singing in a Bunker thematically embodies this. The second chapter “The Art and Inspirations" lists several performances, (installations of) videos and music that have been fundamental to the creation of, and relate to the artistic framework of "Youth Singing in a Bunker." The third and final chapter “How We Spent A Time Together: on the Collaboration” provides an account of the relational process of putting the ensemble together. A contribution to academic writing that shares an insight on ‘how art is made?’ This is an insight that is often overlooked in these kinds of writings.
Keywords: climate crisis; togetherness; performance art; video blogging; music; opinnäytteet; maisterit; fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|